Differences in rectal fecal microbes among Hu sheep, Tibetan sheep, and their hybrid breeds and their relationship with growth traits - Dan Xu; Jiangbo Cheng; Yukun Zhang; Deyin Zhang; Kai Huang; Xiaolong Li; Yuan Zhao; Liming Zhao; Xiaobin Yang; Panpan Cui; Zongwu Ma; Huibin Tian; et al. (Microbiology Spectrum)
ABSTRACT Variety and diversity serve as the foundation for animal husbandry development. Nowadays, heterosis is often used to improve animal performance and increase economic benefits. The intestine is an important organ for nutrient absorption and is also the largest immune organ in the body. Intestinal microorganisms can be influenced by various factors such as animal growth and development stages, gender, health status, feed nutrition level, and host genetic background, among others. In this study, three strains of male sheep, with no significant differences in initial weight at 6 months old, were raised under the same conditions until they reached 9 months of age. We collected the rectal feces of these 9-month-old sheep and compared the differences in rectal fecal microorganisms among the three strains using 16S rDNA sequencing technology. The permutational multivariate analysis of variance test revealed significant differences in microorganisms among different strains. Additionally, we identified six biomarkers in Tibetan sheep and Hu sheep, respectively. Functional enrichment analysis showed that microorganisms may affect the growth traits of sheep through lipid metabolism, and the functional differences among different strains were obvious. Therefore, we believe that crossbreeding can result in the offspring obtaining intestinal microorganisms from their parents to varying degrees, and host heredity is the primary cause of the intestinal microorganism differences.IMPORTANCEIn this study, we identified parental biomarkers by exploring the relationship between parental and hybrid offspring and concluded that these biomarkers may affect related growth traits through fat deposition or lipid metabolism pathways. We also found that hybrid sheep inherited rectal fecal microbes from their parents to varying degrees.